2014
DOI: 10.1080/02755947.2013.860064
|View full text |Cite
|
Sign up to set email alerts
|

Retention of PIT and T‐Bar Anchor Tags in Blue Catfish

Abstract: We quantified retention of PIT and T‐bar anchor tags in Blue Catfish Ictalurus furcatus. Eighty‐one fish (364–1,005 mm TL) were injected with a PIT tag in the dorsal musculature immediately posterior to the dorsal fin and a T‐bar anchor tag below the dorsal fin between the pterygiophores. Fish were held in a 0.24‐ha earthen pond and retention was evaluated at 2, 4, and 6 months. Retention of PIT tags was 100% over the duration of the study. T‐bar anchor tag retention was about 94% at 2 months and 76% at 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Retention of T-bar anchor and PIT tags by least cisco in our study revealed differences between tag types, which is consistent with previous studies (Rude et al, 2011;Bodine and Fleming, 2014). While no PIT tags were shed by least cisco, retention of T-bar anchor tags was high until day 30 (76%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Retention of T-bar anchor and PIT tags by least cisco in our study revealed differences between tag types, which is consistent with previous studies (Rude et al, 2011;Bodine and Fleming, 2014). While no PIT tags were shed by least cisco, retention of T-bar anchor tags was high until day 30 (76%).…”
Section: Discussionsupporting
confidence: 92%
“…Tagging procedures for least cisco followed standard protocols for the implantation and attachment of PIT and T-bar anchor tags, respectively (Rude et al, 2011;Bodine and Fleming, 2014). Fish in the internal implant tag group had a PIT tag (Biomark Model HPT8, 134.2 kHz, 8.4 x 1.4 mm, 0.02 g in air; Biomark, Boise, Idaho) injected into their peritoneal cavity just anterior to the pelvic fins and immediately to the right of the midventral line parallel with the long axis of the body.…”
Section: Fish Taggingmentioning
confidence: 99%
“…Buckmeier and Irwin () found 71% retention after 270 d when Floy FD‐68B anchor tags were used on Channel Catfish (280–379 mm TL). Furthermore, tag retention in Blue Catfish Ictalurus furcatus (364–1005 mm TL) was 76% after 6 months (Bodine and Fleming ), and tag retention was approximately 50% after 250 d for Channel Catfish and Blue Catfish (Timmons and Howell ). Our results suggest that after approximately 6 years (2,196 d), a Channel Catfish population of tagged individuals may retain approximately 54% of the initial tags.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from freeze brands, additional techniques that have been used to mark ictalurid catfishes include plastic tags implanted through dorsal musculature and pterygiophores (Greenland and Bryan 1974;Timmons and Howell 1995;Buckmeier and Irwin 2000;Quinn et al 2012), PIT tags (Moore 1992;Bodine and Fleming 2014), coded wire tags (Heidinger and Cook 1988), and subcutaneous injection of elastomers (Reeves and Buckmeier 2009;Zeller and Cairns 2010). Each method has unique advantages, disadvantages, and expected mark detectability.…”
Section: Discussionmentioning
confidence: 99%